Menulis Kreatif Puisi Di SMP Negeri 13 Makassar Dengan Pendekatan Kooperatif - Hasrianti, Andi (Al-Riwayah : Jurnal Kependidikan, 2016)
: Constructivist approach in cooperative learning model can encourage students to be able to build knowledge together in a group. They are encouraged to find and construct the material being studied through discussion, observation or experiment. Students interpret together what they found or they were discussed. In this way, the subject matter can be built together and not as a transfer of a teacher. Knowledge formed together based on experience and interaction with the environment in the study group, causing mutual enrichment among group members. Students are also able to build and maintain trust, open to receive and impart opinions and ideas, willing to share information and resources, would give support to others with sincerity. Students are also able to lead and skillfully manage the controversy into a problem solving situation, criticize ideas, not a personal one. This cooperative learning model can be implemented properly if one can improve the learning environment that enables among students and between students and teachers feel free opinion and ideas, as well as free in assessing and exploring important topics in the curriculum. Teachers can ask questions or problems that must be solved in the group. Students strive to think hard and discuss each other in the group. Then the teacher and other students can pursue their opinion about his ideas and different perspectives. Teachers also encourage students to be able to demonstrate understanding of the problem issues that were examined by way of the group.